Effeminate belonging : Gender nonconforming experience and gay bottom identities - Vytniorgu, Richard (Emerald Publishing Limited, 2024)
Since the 1970s, effeminate gay men, and fem bottoms in particular, have increasingly become the 'marginalised among the marginalised' in Anglo-American gay culture, which tends to place a premium on appearing, behaving, and sounding masculine. Effeminate Belonging compares how boys and men in Western and global majority contexts negotiate connections between homosexuality, effeminacy, and bottom identity and practice, and why conversations that re-connect sex role positionality and gender expression are important to gay men's sexual wellbeing and sense of belonging. Providing new readings of autobiographical narratives in film, documentary, social media, gay porn, and written erotica, Richard Vytniorgu explores how fem bottoms negotiate gender nonconforming experience and bottom identities in different places and spaces, including in the home, school, LGBTQ+ community, online, and in their own bodies. Consolidating key research on effeminacy and gay bottom identities in the humanities, social sciences, and sciences, this interdisciplinary, cross-cultural, and historical discussion of gay men's sexual and gendered identities offers new insights for readers interested in gender nonconformity, bottoming, and male homosexuality across cultures. Vytniorgu also offers new perspectives for readers interested in connecting socio-cultural and psychobiological dimensions of gender and sexuality, and for health and educational professionals seeking to deepen their knowledge of LGBTQ+ identities and sexual experiences.
Keywords: Gay men -- Developed countries -- Identity.; Effeminacy -- Developed countries.; Gay men -- Developed countries -- Sexual behavior.; Social Science, LGBTQ+ Studies, Gay Studies.; Relating to lesbians.; LGBTQ+ Studies, topics.; Relating to gay people.; elektronické knihy; electronic books